Reading the Exemplum Right : Fixing the Meaning of El Conde Lucanor - Burgoyne, Jonathan, 1967- (Book collections on Project MUSE., 2007)
"Reading the Exemplum Right situates Juan Manuel at the apex of the European literary tradition of the exemplum and demonstrates how he puts the coercive power and authority of the illustrative tale on display for his audience. Following the medieval modes of reading and writing that structure Juan Manuel's text, Jonathan Burgoyne uncovers a rhetorical lesson woven into the entire five-part Conde Lucanor that lays bare the inherent ambivalence of the exemplum as a narrative sign. Burgoyne then traces the earliest response to Juan Manuel's work as it can be uncovered in the layout, variance, interlineations, and marginalia found in the various late medieval and early modern manuscript witnesses of El Conde Lucanor. The study concludes by testing the hypothesis that a work's earliest audience can establish a tradition of reading that effectively prevents alternative interpretations and fixes an orthodox meaning of the text for future generations."--Provided by publisher